2005
DOI: 10.1172/jci22518
|View full text |Cite
|
Sign up to set email alerts
|

CaV2.3 calcium channels control second-phase insulin release

Abstract: Concerted activation of different voltage-gated Ca 2+ channel isoforms may determine the kinetics of insulin release from pancreatic islets. Here we have elucidated the role of R-type Ca V 2.3 channels in that process. A 20% reduction in glucose-evoked insulin secretion was observed in Ca V 2.3-knockout (Ca V 2.3 -/-) islets, close to the 17% inhibition by the R-type blocker SNX482 but much less than the 77% inhibition produced by the L-type Ca 2+ channel antagonist isradipine. Dynamic insulin-release measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
163
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(173 citation statements)
references
References 54 publications
10
163
0
Order By: Relevance
“…In addition, first-phase secretion from wild-type cells has been found to occur mainly from previously docked granules at Synt1A-rich locations, whereas second-phase secretion is mainly due to newcomer granules fusing away from Synt1A clusters (14). Because syntaxin-1 and L-type Ca 2ϩ channels colocalize (39), the results of Ohara-Imaizumi et al (14) show that first-phase secretion takes place mostly at L-type Ca 2ϩ channels, whereas second-phase fusion events occur away from L-type channels, in accordance with Ca 2ϩ -channel knockout experiments (10,11).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…In addition, first-phase secretion from wild-type cells has been found to occur mainly from previously docked granules at Synt1A-rich locations, whereas second-phase secretion is mainly due to newcomer granules fusing away from Synt1A clusters (14). Because syntaxin-1 and L-type Ca 2ϩ channels colocalize (39), the results of Ohara-Imaizumi et al (14) show that first-phase secretion takes place mostly at L-type Ca 2ϩ channels, whereas second-phase fusion events occur away from L-type channels, in accordance with Ca 2ϩ -channel knockout experiments (10,11).…”
supporting
confidence: 58%
“…Resupply in this view is an element in the amplifying pathway because it increases the effectiveness of calcium (8,9). Knockout studies have shown that L-type Ca 2ϩ channels control first-phase secretion (10), whereas other types, such as R-type channels, are important for the second phase (11). Classically it has been thought that newly arrived vesicles must go through a sequence of steps, docking and priming, before fusing (12), but more recent data suggest that newcomers fuse with only a short delay during the second phase (13)(14)(15).…”
mentioning
confidence: 99%
“…Our measurements where performed in the presence of cAMP where exocytosis is mainly dependent on influx though L-type Ca 2+ -channels [6,14]. The beta-cell Ca 2+ -current reduced by the antibody was a non-L-type and most likely a R-type Ca 2+ -current [36] and alpha-cells do not contain R-type Ca 2+ -channels [19]. Thus, it is not surprising that the antibody did not interfere with the Ca 2+ -influx in the alpha-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Exocytosis of primed granules in the RRP of the alpha-cell is controlled by influx of Ca 2+ through N-type Ca 2+ -channels in the absence of cAMP, and through L-type Ca 2+ -channels in the presence of high levels of cAMP [6,14]. In mouse beta-cells, rapid exocytosis is under the control of L-type Ca 2+ -channels whereas refilling of granules is controlled by influx through Rtype Ca 2+ -channels [19]. Other than directly affecting exocytosis, SNAP-25 and syntaxin 1A have also been suggested to modulate the voltage-dependent Ca 2+ channels [9,16], however with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic beta cells express several types of VDCCs in humans and rodents, including the L-type Ca V 1.2 and R-type Ca V 2.3 [15,16]. Studies in rodent models have demonstrated that these channels play distinct roles for the characteristic biphasic insulin release pattern and while Ca V 1.2 evokes the first phase [17], the Ca V 2.3 is considered responsible for sustained second-phase insulin release [18]. Mice lacking the Ca V 2.3 channel suffer from fasting hyperglycaemia and reduced glucose clearance [19,20].…”
Section: Introductionmentioning
confidence: 99%